1993
DOI: 10.1055/s-2007-997925
|View full text |Cite
|
Sign up to set email alerts
|

Testosteron- versus Dihydrotestosteron-Effekte auf permanente Plattenepithelkarzinomzellinien des Larynx

Abstract: Whereas stimulating effects of androgenic hormones on the laryngeal mucosa and their tumours have been reported in the literature, we are faced with the highest incidence of laryngeal carcinomas in the presence of a reduced androgen signal from the testes associated with aging. The discrepancies between reports in the literature and our own recent experiences with in vitro application of testosterone on permanent laryngeal squamous carcinoma cell lines, initiated this current examination of testosterone, dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
2
Order By: Relevance
“…Despite a variety of factors known to promote malignant changes in the laryngeal mucosa (eg, tobacco smoke, excessive alcohol consumption, occupational exposure to dusts, gases, and smoke4, 16–18) these factors do not explain sufficiently the imbalance between the sexes in the occurrence of the disease. So far, the hypothesis of hormone dependency of laryngeal carcinoma has not been proved 10–12, 19–22…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a variety of factors known to promote malignant changes in the laryngeal mucosa (eg, tobacco smoke, excessive alcohol consumption, occupational exposure to dusts, gases, and smoke4, 16–18) these factors do not explain sufficiently the imbalance between the sexes in the occurrence of the disease. So far, the hypothesis of hormone dependency of laryngeal carcinoma has not been proved 10–12, 19–22…”
Section: Discussionmentioning
confidence: 99%
“…A range of studies describing sex hormone concentrations in patients with cancer of the larynx have not brought clear results. Some authors suggested hyperandrogenism or hypoandrogenism as factors predisposing to laryngeal carcinoma; others emphasized the role of an imbalance between total testosterone and DHT 11, 21. Fillipov et al23 found low levels of total testosterone in each of 166 examined patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In einer offensichtlichen Mangelsituation käme auch die Substitution von Testosteron in Frage. In Anbetracht der eher zytostatisch als zytotoxischen Wirkungen der Sexualsteroide auf die Tumorzelle [15] scheint eine Anwendung bei ausgedehnten Tumoren nicht sinnvoll. Hoffnungen können u. E. für die Behandlung von Praneoplasien bzw.…”
Section: Diskussonunclassified
“…Deitmer (1983) beobachtete zwei Typen von Frauen mit Larynxkarzinomen: ältere Frauen, die rauchten, und jungere Frauen, die Zeichen einer Virilisierung aufwiesen (6). Schon Jahrzehnte wird uber den Zusammenhang der Genese von Laiynxkarzinomen und Veränderungen der Androgen/Ostrogenbalance diskutiert (10,19). Untersuchungen an normalem Larynxgewebe, das ja hormonaktiv ist, zeigten einen Uberwiegen- Angaben ttber die Rauch-und Trinkgewohnheiten wurden der Ananmese entnommen.…”
Section: Einieitungunclassified